Peak torque, rate of torque development and average torque of isometric ankle and elbow contractions show excellent test-retest reliability - Daniel Simpson; Monika Ehrensberger; Christopher Nulty; Joanne Regan; Patrick Broderick; Catherine Blake; Kenneth Monaghan (World Scientific Publishing, 2019)
Background: Peak Torque (PT), Rate of Torque Development (RTD) and Average Torque (AT) over a single contraction assess the three components of muscle function during isometric contractions. Surprisingly, AT has never been reported or its reliability confirmed. Objectives: This study aims to establish protocol reliability for ankle dorsiflexion and elbow extension isometric muscle function (PT, RTD, AT) in healthy participants using the Biodex System 3 Dynamometer. Methods: Twelve participants (6 male, 6 female, mean age 39.8±16.0 years) performed four maximal isometric contractions on two occasions. Intraclass Correlation Coefficient (ICC), Typical Error (TE) and Coefficient of Variation (CV) for PT, RTD and AT were reported. Results: The ICC for all strength parameters varied from 0.98-0.92. TE for ankle dorsiflexion PT was 1.38Nm, RTD 7.43Nm/s and AT 1.33Nm, CV varied from 6.26±6.25% to 11.72±8.27%. For elbow extension, TE was 3.36Nm for PT, 14.87Nm/s for RTD and 3.03Nm for AT, CV varied from 5.97±4.52% to 18.46±14.78%. Conclusion: Maximal isometric ankle dorsiflexion and elbow extension PT, RTD and AT can be evaluated with excellent reliability when following the described protocol. This testing procedure, including the application of AT, can be confidently applied in research, exercise or clinical settings.